Customizing and Evaluating Accessible Multisensory Music Experiences with Pre-Verbal Children—A Case Study on the Perception of Musical Haptics Using Participatory Design with Proxies - Emma Frid; Claudio Panariello; Claudia Núñez-Pacheco (Multimodal Technologies and Interaction, 2022)
Research on Accessible Digital Musical Instruments (ADMIs) has highlighted the need for participatory design methods, i.e., to actively include users as co-designers and informants in the design process. However, very little work has explored how pre-verbal children with Profound and Multiple Disabilities (PMLD) can be involved in such processes. In this paper, we apply in-depth qualitative and mixed methodologies in a case study with four students with PMLD. Using Participatory Design with Proxies (PDwP), we assess how these students can be involved in the customization and evaluation of the design of a multisensory music experience intended for a large-scale ADMI. Results from an experiment focused on communication of musical haptics highlighted the diversity in employed interaction strategies used by the children, accessibility limitations of the current multisensory experience design, and the importance of using a multifaceted variety of qualitative and quantitative methods to arrive at more informed conclusions when applying a design with proxies methodology.